Guillain-Barré syndrome - Silvi Afifah; Basli Muhammad (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Guillain-Barré Syndrome (GBS) is a serious but rare post-infectious immune-mediated neuropathy. This disease is caused by autoimmune damage to nerves in the peripheral nervous system causing symptoms such as numbness, tingling, and weakness that can progress to paralysis. The incidence of GBS is 0.42 cases per 100,000 people. The highest incidence occurs in adolescents and the elderly at the age of 50 years. While in children, cases with Acute Flaccid Paralysis occur in 25.9% - 50% of children. So the incidence of GBS in children is 0.34 cases per 100,000 children. If it attacks children, they will experience progressive motor development disorders, and can even cause death. The most effective therapy is generally intravenous immunoglobulin (IVIG). In general, the outcome of GBS is more favorable in children than in adults; however, the recovery period is long, often weeks to months.